2013
DOI: 10.1111/bju.12133
|View full text |Cite
|
Sign up to set email alerts
|

Patient characteristics and outcomes in metastatic upper tract urothelial carcinoma after radical nephroureterectomy: the experience of Japanese multi‐institutions

Abstract: Objectives• To investigate oncological outcomes and prognostic factors in patients with upper tract urothelial carcinoma (UTUC) who experienced disease recurrence after radical nephroureterectomy (RNU).• Few studies have focused on the clinical courses of patients who experienced disease recurrence after RNU. Patients and Methods• A total of 204 UTUC patients who experienced disease recurrence from a retrospective multi-institutional cohort were included in the present study.• Associated patient outcomes were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 30 publications
2
32
0
1
Order By: Relevance
“…Previous literatures have shown the survival prediction for metastatic UC after chemotherapy, mainly focusing on UCB [18][19][20][21][22][23][24][25][26]. There were limited studies to separately investigate or compare the prognostic factors between metastatic UTUC and UCB after cisplatin-based chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Previous literatures have shown the survival prediction for metastatic UC after chemotherapy, mainly focusing on UCB [18][19][20][21][22][23][24][25][26]. There were limited studies to separately investigate or compare the prognostic factors between metastatic UTUC and UCB after cisplatin-based chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, older UTUC patients receive systemic chemotherapy when recurrence/metastasis occurs. The mean ages of patients with recurrence and/or metastasis after total cystectomy and RNU were previously reported to be 65-66 years (22,23) and 72 years (24), respectively. Furthermore, due to a solitary functioning kidney after RNU, patients with recurrent/ metastatic UTUC were found to have lower renal function and, hence, non-cisplatin-based chemo-regimen was more likely to be selected.…”
Section: Discussionmentioning
confidence: 99%
“…Several major prognostic models were also validated by using our cohort, including the Bajorin model, 15 Taguchi model 16 and Tanaka model. 17 Harrell's c-index was calculated to evaluate their predicting performances.…”
Section: Discussionmentioning
confidence: 99%
“…Tanaka et al reported that PS, the presence of liver metastasis and the number of recurrence sites were independently related to poor survival of mUTUC after chemotherapy. 17 However, 17% received non-cisplatin-based chemotherapy. In the present study, we suggest that renal function, performance status, liver metastasis and number of metastatic sites have a significant impact on survival for mUTUC patients treated with cisplatin-based chemotherapy.…”
Section: Discussionmentioning
confidence: 99%